ANXIETY EFFECTS OF SELF-CONFIDENCE IN EFL SPEAKING SKILL - Desti Rahmawati; Rissa San Rizqiya (IKIP Siliwangi, 2023)
Speaking sometimes considered as the display of oneâ€™s language proficiency, the more proficient s/he speaks the better is his/her language skill. Speaking can be influenced by several aspects of psychology as self-confidence. People who have higher fear and lower of confidence in speaking English have difficulties in performing their speaking skill ability. This study is to investigate the effects of anxiety on self-confidence in English as Foreign Language speaking skill. This study is a qualitative study where the data were obtained from closed-ended questionnaire and open-ended questionnaire. The participants of this research were 35 students aged 20-23 years old. The data result was evaluated descriptively, while the open-ended question questionnaire was processed line by line to produce and build codes and themes. The questionnaires showed that five themes were related to students' anxiety in speaking English, which resulted in a lack of self-confidence; among all are lack of vocabulary, lack of self-esteem, a fear of negative reaction, a fear of judgment from the lecturer, and teacher-centered classroom.Â Keywords:Â Speaking; Foreign language; Anxiety; Self-confidence